2014
DOI: 10.1080/0966369x.2014.885889
|View full text |Cite
|
Sign up to set email alerts
|

Participatory video drama research in transitional Vietnam: post-production narratives on marriage, parenting and social evils

Abstract: Based on two years of participatory video drama (PVD) research with men and women in the city of Huế, this article explores perspectives on, and experiences of, socioeconomic transition and its influence on domestic life in Vietnam. Through a combination of output analysis, group screening sessions and individual interviews, it concentrates on the themes of marriage, parenting and 'social evils' which emerged in the PVD. It demonstrates how familial tensions collectively identified in the workshop and told in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Indeed, PAR scholars struggle with how analysis highlights researchers' views over participants', reiterating centre-periphery binaries and privileges. Kathryn Brickell (2015) addresses this explicitly, by writing the different analyses of research (by herself, and by local people) separately, and reflecting on these. Thus a plurality of voices are presented, situating herself, as white western academic, simultaneously through diverse readings of research themes among variously positioned participants.…”
Section: Limitationsmentioning
confidence: 99%
“…Indeed, PAR scholars struggle with how analysis highlights researchers' views over participants', reiterating centre-periphery binaries and privileges. Kathryn Brickell (2015) addresses this explicitly, by writing the different analyses of research (by herself, and by local people) separately, and reflecting on these. Thus a plurality of voices are presented, situating herself, as white western academic, simultaneously through diverse readings of research themes among variously positioned participants.…”
Section: Limitationsmentioning
confidence: 99%
“…Rates of divorce are rising in Vietnam and women are increasingly becoming more confident in their choice to raise children by themselves (or alongside family members) rather than in challenging “nuclear family” arrangements (Brickell ). Showing off in a street space intoxicated by alcohol is not a throwaway type of fieldwork space but reveals some men's coping strategies in a country that is undergoing significant social transformations, and in particular in the area of women's equality issues (more on this below; see also Brickell ; Drummond and Rydstrom ; Leshkowich ; Rydstrom , ).…”
Section: Chúc Sc Khóe (“To Good Health”): Whiteness and Masculinity Imentioning
confidence: 99%
“…The production of these geographies in Vietnam is documented below through a discussion of an ethically troublesome consumer good: the alcoholic beverage. Through three representative vignettes from the field I demonstrate that whiteness and masculinity are not only polarizing ideas affecting research in geography in North America and Europe but are threaded deeply in the research ethics fabric among geographers conducting fieldwork in countries in the global South like Vietnam (see Brickell , ; Scott and Chuyen ; Scott et al ). I offer a sympathetic critique of work that renders problematic the “ways that we as critical geographers (re)produce white supremacy” (Berg :509) and a discipline that produces “geographical research [that] has in effect been passively, often inadvertently, sexist” (Monk and Hanson :11) by writing a feminist inspired paper that reconfigures the white, male geographer as a character that moves beyond the subaltern‐hegemonic binary in the conduct of fieldwork.…”
Section: Introductionmentioning
confidence: 99%
“…When they produce a story, they are the ones 'directing' rather than men, thus altering gender roles. Some researchers have sought to understand how producing participatory video drama enables women to explore power relations and express themselves (Brickell, 2014;Waite & Conn, 2011). Some studies on PV with women have shown how by the end of the PV projects, women had gained more voice and confidence, and raised social issues (Bery & Stuart, 1996; Khamis, Plush, & Sepulveda Zelaya, 2009).…”
Section: Participatory Video Gender and Agencymentioning
confidence: 99%